METAGENOMICS ANALYSIS OF MICROBIOTA ON PATIENT CASE STUDIES IN WEST JAVA FOR THE DEVELOPMENT OF BIOMARKER CANDIDATES OF COVID-19 SEVERITY - Mellyani, Karlina
Coronavirus Disease - 2019 (COVID-19) was declared as a global pandemic in March 2020 by WHO. Symptoms caused by COVID-19 are very diverse ranging from asymptomatic, to causing death.. The severity level of COVID-19 might cause by coinfection of microorganisms. Therefore, this study was conducted to compare the abundance profile of microorganisms in symptomatic compared to asymptomatic COVID-19 patients, so the development of biomarkers for detection of the severity of COVID-19 patients can be obtained. The study was conducted on four patientswith two symptomatic patients(S1 and S2) and two asymptomatic patients(A1 and A2). Each sample has four technical replicates of paired-end data sequencing results. The determination of biomarkers was done by shotgun sequencing method using the Illumina Stranded Total RNA Prep protocol and ligation with Ribo-ZeroTM Plus on the Illumina NextSeq 550 (Illumina, USA). The fastq as the output of sequencing then proceed using BBduk plugin in Geneious Prime v.2020.2 software for trimming the reads less than 70bp and low quality (<30 is using Kraken 2 program with minikraken_8GB_20200312 databases. Microorganism is mapped to databases of archaea, bacteria, and viruses. The output of kraken2 is then processed using Kraken-biom in R studio (ver 4.1.1) and visualize the total abundance using ggplot2 package. Diversity analysis was also conducted using alpha and beta diversity packages in ggplot2. To compare the increase in sample abundance in one sample group compared to another sample group, data was proceeed with DESeq2. The output of DESeq2 were log 2 fold change (log2fc) and p-value. These data then visualized with enhanced volcano plot, networking, and heatmap. The results showed Veillonella parvula (98 species in both of symptomatic patients) had a significantly increased (P<0.01) in symptomatic samples compared to asymptomatic samples. In addition, Streptococcus pneumoniae (197269 species in both of symptomatic patients and 18 species in both of asymptomatic patients), Haemophilus influenzae (8511 species in both of symptomatic patients and 11 species in both of asymptomatic patients), and Staphylococcus cohnii (14659 species in both of symptomatic patients and 62 species in both of asymptomatic patients) increased significantly (P<0.01) in symptomatic patients who had symptoms of shortness of breath (patient S1). Therefore, in this study can be obtained several diagnostic biomarker candidates for the molecular method real time Polymerase Chain Reactions (rt-PCR). Veillonella parvula as a biomarker candidate in symptomatic patients, as well as S.pneumoniae, H.influenzae,and S.cohnii in patients with shortness of breath.